INCORPORATE ETHICS INTO STRATEGIC MANAGEMENT:THE PRINCIPLES OF GENERATION Y - Sitikantha Mishra , Bibhuti B Pradhan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Generation Y, also known as the Net Generation or Millennials, refers to a population collaborator greater than that of the Baby Boom generation. With around 80 million people born between the mid-1980s and 2000, this group is the most recent generation to enter the workforce. Workplaces are being redefined and companies are being encouraged to adapt as this latest generation of workers inspires enterprises. It is widely accepted that distinct generational experiences shape ethical ideologies and therefore, in turn, ethical ideologies affect the way people function in the workplace. Differences of perspective based on age, and complaints about other generations are certainly not a new phenomenon. Companies committed to high standards of ethics know how important it is to build a common sense of values and a cohesive community grounded in honesty, where principles of organization and personal values match. Generation develops its own unique viewpoint on what constitutes right and wrong behaviour on the job, influenced by significant events, social patterns and the cultures on their organisations. Accordingly, the shared experiences of collaboration with Gen Y are likely to influence their ethical values and consequent decisions and behaviour at the workplace. In this study, research examine the ethical ideology of Gen Y, and its reflections on essential strategic management. This community of people is an important part of the workforce, since they are the business lives near future managers. The study goal is to better understand the impacts of the ethical philosophy of Generation Y and how this philosophy affects their business practice.